Prenatal Nicotine Exposure Increases GABA Signaling and Mucin Expression in Airway Epithelium - Fu, Xiao Wen (American Thoracic Society, 2011)
Maternal smoking during pregnancy increases the risk of respiratory disease in offspring, but surprisingly little is known about the underlying mechanisms. Nicotinic acetylcholine receptors (nAChRs) expressed in bronchial epithelial cells (BECs) mediate the effects of nicotine on lung development and function. Recently, BECs were also shown to express a GABAergic paracrine loop that was implicated in mucus overproduction in asthma. We therefore investigated the interactions between cholinergic and GABAergic signaling in rhesus macaque BECs, and found that nicotine upregulated GABA signaling in BECs through the sequential activation of BEC nAChR and GABA receptors. The incubation of primary cultures of rhesus BECs increased concentrations of GAD, GABA(A) receptors, and mucin mRNA. The nicotine-induced increase in glutamatic acid decarboxylase (GAD) and GABA(A) receptor mRNA resulted in increased GABA-induced currents and increased expression of mucin. The ability of nicotine to increase mucin expression was blocked by nicotinic and GABA(A) antagonists. These results implicate GABA signaling as a middleman in nicotine's effects on mucus overproduction. Similar effects of nicotine on GABA signaling and the expression of mucin were seen in vivo after chronic exposure of rhesus monkeys to nicotine. These data provide a new mechanism linking smoking with the increased mucin seen in asthma and chronic obstructive pulmonary disorder, and suggest a new paradigm of communication between non-neuronal transmitter systems in BECs. The existence of neural-like transmitter interactions in BECs suggests that some drugs active in the central nervous system may possess previously unexpected utility in respiratory diseases.